The effect of heterogeneity in sedimentary properties on fluid flow behaviour at the pore-scale - Jones, F.E (2022)
Sandstone reservoir rocks are important for numerous applications, such as oil and gas recovery, CO2 storage and groundwater aquifers, and understanding how reservoir rock properties influence the dynamics of fluids and gases within reservoir rocks is essential yet difficult to predict. Heterogeneity complicates the identification of viable areas of recovery, potential areas of migration and groundwater catchment planning. To improve accuracy in reservoir flow models further analysis of the impact of heterogeneous reservoir rock properties on fluid transport is required. Pore network analysis is key in understanding fundamental concepts of fluid flow behaviour as pore network geometry is a dominant control on the effectiveness of fluid transport within a reservoir and is strongly associated with porosity and permeability. Despite this, there has been limited research into how heterogeneous rock properties influence fluid flow behaviour at the pore scale and analysis is commonly focused on samples which have homogeneous grain size and mineralogy.